(untitled) (Abhat Journal, 2025)
This study addressed the role of free zone management in attracting foreign investments, applying it to the Sirte Free Zone, The Free zone is one of the most important targets for attracting foreign investment as it provides the facilities and privileges for investors, and driving development across all sectors in the country, The study adopted the descriptive analytical approach using a questionnaire as an instrument for collecting data. The data was analyzed using the Statistical Program for Social Sciences (SPSS). The study’s findings revealed that the level of senior management support for the development of the free zone has increased. The results also revealed a positive regulatory climate with regulations and laws showing the strongest attracting in significant foreign investment. It was also evident that employee participation in training courses is not good, which may limit their ability to create a sophisticated investment environment. The study’s recommends reinforcing necessary the laws and legislation related to free zones as well as ranting transparency as they are essential in attracting investors, It is also necessary the focus on developing the internal regulatory climate by enhancing transparency and facilitating administrative procedures for investors. The free zone’s strategic plans must also be restructured to be more closely aligned with global markets and their changes.